1991
DOI: 10.2135/cropsci1991.0011183x003100020037x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Salinity Responses among Pigeonpea Genotypes and Their Wild Relatives

Abstract: Soil salinity can be a major constraint to pigeonpea (Cajanus cajan (L.) Millsp.) in the regions where it is predominantly grown. This study was conducted to assess the extent of genetic variation for salinity tolerance in the germplasm of pigeonpea and its wild relatives. Solution culture experiments in a greenhouse and controlled environment chamber were conducted to screen a range of cultivated pigeonpea genotypes for ability to germinate and grow up to 60 d under saline conditions. Several wild relatives o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
23
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 0 publications
3
23
0
Order By: Relevance
“…The genotypes which were found highly tolerant or tolerant and highly sensitive in both in vitro and in vivo conditions under water logging and saline conditions can be used for developing appropriate populations for genetic studies. Subarao et al [6] studied comparative salinity tolerance among pigeonpea genotypes and their wild relatives. A large genetic variation was also observed earlier in cultivated and wild species of pigeonpea, especially C. scarabaeoides, for salinity tolerance [5].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The genotypes which were found highly tolerant or tolerant and highly sensitive in both in vitro and in vivo conditions under water logging and saline conditions can be used for developing appropriate populations for genetic studies. Subarao et al [6] studied comparative salinity tolerance among pigeonpea genotypes and their wild relatives. A large genetic variation was also observed earlier in cultivated and wild species of pigeonpea, especially C. scarabaeoides, for salinity tolerance [5].…”
Section: Discussionmentioning
confidence: 99%
“…These abiotic stresses adversely affect its productivity causing severe yield losses [1,2]. Pigeonpea is reported to be highly sensitive to water logging [3,4] and salinity [5,6]. Water logging and salinity stresses are important yield constraints in pigeonpea as water logging blocks oxygen supply to roots which hampers root permeability [7] and salinity impairs seed germination, reduces nodule formation, retards plant development and finally reduces crop yield [8].…”
Section: Introductionmentioning
confidence: 99%
“…These are very sensitive to salt levels and soil drought status, experiencing water deficit due to osmotic stress possibly coupled with biochemical perturbations induced by the influx of sodium ions. Some of the leguminous plants like faba bean (Abdel Ghaffar et al 1982), chickpea (Lauchli 1984), tepary bean (Coons and Pratt 1988), pigeon pea (Subbarao and Johansen 1991) and common bean (MorenoLimo´n et al 2000) have been reported to show salt tolerance. However, the reports on the salt tolerance in mustard genotypes are meager.…”
Section: Introductionmentioning
confidence: 99%
“…These are very sensitive to salt levels and soil drought status, experiencing water deficit due to osmotic stress possibly coupled with biochemical perturbations induced by the influx of sodium ions. Some of the leguminous plants, like faba bean (Abdel-Ghaffar et al 1982), chickpea (Lauchli 1984), tepary bean (Coons and Pratt 1988), pigeon pea (Subbarao and Johansen 1991) and common bean (Moreno-Limon et al 2000) have been reported to show salt tolerance. However, reports on the salt tolerance in soybean genotypes are meagre.…”
Section: Introductionmentioning
confidence: 99%